Laser ablation behavior and mechanism of C/SiC coated with ZrB2 –MoSi2–SiC/Mo prepared by HVOF. Issue 11 (1st August 2020) - Cheng, Su; Geng, Li; Liu, Xiaochong; Wang, Yiguang
Abstract: Recently, carbon fiber-reinforced silicon carbide (C/SiC) composites are considered important candidates for laser protection materials. In this paper, the ablation mechanism of C/SiC composites and their modified composites under laser irradiation was studied. ZrB2 –MoSi2 –SiC ternary-phase ceramic was successfully coated on C/SiC composites by using high velocity oxygen fuel (HVOF) technology, with Mo as transition layer. The evolution of phase and morphology of the composites was investigated by X-ray diffraction, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The ablation behavior of composites was investigated by laser confocal microscopy (LCM). The results showed that the ablation mechanism of composites was controlled by phase transformation, thermal reaction and thermal diffusion. The solid-liquid transition of ZrB2 and MoSi2 was the dominant factor. Thermal reaction and good thermal diffusivity of coatings were also important factors affecting the ablation performance. ZrB2 –SiC– MoSi2 /Mo coating failed when all phase transitions were completed and no continuous liquid phase was formed, followed by rapid damage of C/SiC substrate. The results of this work can provide theoretical guidance and research ideas for the design and application of laser protective materials.